IMAGES OF OBJECTS AND LANDSCAPES IN THE NOVEL “JANE EYRE” BY CHARLOTTE BRONTE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the issue of imagery in the famous novel "Jane Eyre" by feminist writer, a brilliant figure in English literature Charlotte Bronte who lived in the nineteenth century. It is given ideas how the writer can deliver the effective use of images of landscapes, objects, places and even animals for showing inner emotional feelings of main character to the reader.